"You Have Witchcraft on Your Lips" : how a coven of white, Afrikaans-speaking witches negotiate their craft in the context of past and present - McNeill, Fraser G. (University of Pretoria, 2020)
Mini Dissertation (MA)--University of Pretoria, 2019.